HUBUNGAN KUALITAS PELAYANAN JASA TERHADAP KEPUASAN KONSUMEN PENGGUNA JASA PT. FRES INDONESIA (TRANSPORTATION, RENTAL CAR, AND BUS) BANDUNG - Hasti Pramesti Kusnara (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2018)
One of the infrastructure that has grew is the highway that experienced rapid development , it can be seen from the emergence of the freeway that connects the city with other cities and the construction of new roads is carried up to the rural outposts , motor vehicle especially four wheel drive vehicles or cars have held an important role in society as a means of transportation . The growth of the national automotive industry has influenced the rapid car rental business in Indonesia. To win the competition is getting tougher PT . Fres INDONESIA ( TRANSPORTATION , RENTAL CAR , and BUS ) should be able to improve the quality of service , but in fact the quality of PT services. Fres INDONESIA is evidenced by the still low number of complaints from consumers . It makes basic PT . Fres INDONESIA ( TRANSPORTATION , RENTAL CAR , and BUS ) to further improve its service to satisfy all our customers , because it is basically an attempt to satisfy consumer is an effort to develop the quality of the goods or services of the company to satisfy the needs of consumers who meet or exceed the criteria desired by consumers . In this study the method used is descriptive method is the method by providing a systematic overview , factual , and accurate information on the facts and the correlation between the variables studied. Hypothesis test results t value greater than t table, then Ho is rejected and Ha is accepted , it means the quality of services affect customer satisfaction . Keywords : Quality Care Services , Consumer Satisfaction